The Status of Triorophus punctatus LeConte (Coleoptera: Tenebrionidae: Pimeliinae: Edrotini) - Aalbu, Rolf L.; Wirth, Christopher C. (Zootaxa, 2019)
While working on a revision of Triorophus LeConte, 1851 we examined type material for the genus. One species, Triorophus punctatus LeConte, 1851 (Figs. 1a–1e), was described from a dead, partial specimen (Type 4475, Museum of Comparative Zoology, Harvard University) collected at “Vallecitas,” California in October or November of 1850 (LeConte, 1851). The locality likely refers to Vallecito, a contemporary United States Army depot and stage station (Roberts, 1988) located on the western edge of the Colorado Desert in eastern San Diego County (32.9755°, -116.35°).